Application of the Translation Theory Explicitation and Implicitation in Translation Result of the Short Story Die Verwandlung - Tamara Aurelia Gita Kartika; Rosyidah Rosyidah (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2023)
This study is aimed to describe: 1) application of the Explicitation and Implicitation translation theory in translation result of the short story Die Verwandlung, and 2) the translation technique used by the translator to put explicitation and implicitation theory into practice. This study used a descriptive qualitative method. The study found that explicitation theory applied in 4 form: 1) lexical unit addition, 2) replacement of general SL unit with more specific TL unit, 3) structural shift in TT, and 4) one sentence from ST divided into 2 or several sentences in the TT. In addition, there are 2 form of Implicitation theory: 1) deletion of the SL unit, and 2) replacement of a specific SL unit with a more general TL unit. The study found that the translator uses 6 translation techniques that consist of addition, amplification, particularization, transposition, deletion, and generalization.